Modeling association between times to recurrence of the different polarities in bipolar disorder among service seekers in urban Nigeria: a survival analysis approach (2017)
Introduction: Bipolar disorder (BD) remains both a clinical and public health challenge worldwide, especially in developing countries such as Nigeria. Many studies have focused on prevalence and recurrences among BD service seekers but little has been documented on the nature, strength, direction, existence, and estimation of association between times to recurrence of the two possible polarities or mood episodes in BD. In this study, we explored the association between durations before recurrence of depression and manic episodes among people seeking treatment for BD. Methods: This analytical study used retrospective data of 467 persons who sought treatment for BD at the psychiatric clinic of University College Hospital, Ibadan, Nigeria between 2005 and 2014. Descriptive statistics were used to explore the data. We right-censored the data and obtained Kaplan–Meier estimates of the time to recurrence of the outcomes and transformed the estimates to standardized binormal data using quantile-quantile transformation. The likelihood was maximized to obtain the maximum likelihood estimate of the association parameter at 5% significance level. Results: The mean (± standard deviation) age of the respondents was 32.9±12.9 years, this was lower among service seekers who were initially diagnosed with mania than among those initially diagnosed with depression (31.3±11.6, 33.2±11.9, respectively). The median survival time to recurrence of mania and depression among the patients was 1,120 and 745 days, respectively, whereas association between times to recurrence of mania and depression was maximized at 0.67 (95% confidence interval: 0.62–0.71). Conclusion: There exists a strong and positive association between times to recurrence of depression and mania in BD. The longer the time to recurrence of mania, the longer the time to recurrence of depression and vice versa.